Augmented Reality User Interfaces: Analyzing Design Principles and Evaluation Methods for Augmented Reality (AR) User Interfaces to Enhance User Interaction and Experience (Human-Computer Interaction Perspectives, 2024)
Augmented Reality (AR) has emerged as a transformative technology that overlays digital content onto the real world, offering unique user experiences. Designing effective AR user interfaces (UIs) requires careful consideration of interaction principles and evaluation methods to ensure usability and user satisfaction. This paper explores the design principles and evaluation methods for AR UIs, aiming to enhance user interaction and experience. It discusses the challenges and opportunities in AR UI design and presents a framework for evaluating AR UIs. The paper concludes with recommendations for future research directions in AR UI design and evaluation.
Keywords: Augmented Reality; User Interface Design; User Experience; Interaction Design; Evaluation Methods; Usability; User Interaction